PREDIKSI DAN PENGUKURAN KERUGIAN TEKANAN AIR MENGALIR DI DALAM SALURAN MIKRO SEGI EMPAT - M. Mirmanto (Dinamika Teknik Mesin, 2013)
This paper presents experimental results of pressure drop measurement and prediction of water flowing through a copper rectangular microchannel with a hydraulic diameter of 437 µm. The aim of this work is to identify discrepancies between experimental data and macrochannel theory. An inlet temperature of 60oC was kept constant at the channel entrance and the experiments were performed with Reynolds numbers (based on the mean velocity and hydraulic diameter) ranging up to 4500.  The results show that the pressure drop prediction agrees with the theory. However, the trend of Poiseuille number with the Reynolds number was not constant for laminar flow. This could be due to the entrance effect. Moreover, the friction factor theory could predict the experimental data for turbulent flow. Thus, in this experiment, the theory for flow in macro passages is still applicable.